The Impact of Complex Volcanic Plumbing on the Nature of Seismicity in the Developing Magmatic Natron Rift, Tanzania - Reiss, Miriam Christina; Muirhead, James D.; Laizer, Amani S.; Link, Frederik; Kazimoto, Emmanuel O.; Ebinger, Cynthia J.; Rümpker, Georg (Frontiers in Earth Science, 2021)
Constraining the architecture of complex 3D volcanic plumbing systems within active rifts, and their impact on rift processes, is critical for examining the interplay between faulting, magmatism and magmatic fluids in developing rift segments. The Natron basin of the East African Rift System provides an ideal location to study these processes, owing to its recent magmatic-tectonic activity and ongoing active carbonatite volcanism at Oldoinyo Lengai. Here, we report seismicity and fault plane solutions from a 10-month temporary seismic network spanning Oldoinyo Lengai, Naibor Soito volcanic field and Gelai volcano. We locate 6827 earthquakes with ML -0.85 to 3.6, which are related to previous and ongoing magmatic and volcanic activity in the region, as well as regional tectonic extension. We observe seismicity down to ~17 km depth north and south of Oldoinyo Lengai and shallow seismicity (3 - 10 km) beneath Gelai, including two swarms. The deepest seismicity (~down to 20 km) occurs above a previously imaged magma body below Naibor Soito. These seismicity patterns reveal a detailed image of a complex volcanic plumbing system, supporting potential lateral and vertical connections between shallow- and deep-seated magmas, where fluid and melt transport to the surface is facilitated by intrusion of dikes and sills. Focal mechanisms vary spatially. T-axis trends reveal dominantly WNW-ESE extension near Gelai, while strike-slip mechanisms and a radial trend in P-axes are observed in the vicinity of Oldoinyo Lengai. These data support local variations in the state of stress, resulting from a combination of volcanic edifice loading and magma-driven stress changes imposed on a regional extensional stress field. Our results indicate that the southern Natron basin is a segmented rift system, in which fluids preferentially percolate vertically and laterally in a region where strain transfers from a border fault to a developing magmatic rift segment.